K historii jednoho typu - Josef Dohnal (Opera slavica)
The article deals with the development of a literary type of the "spineless" man in the Russian literature of the 19th and 20th century taking as samples three literary heroes: Molchalin (the comedy Горе от ума by A. S. Gribojedov), Ochumelov (short story Хамелеон written by A. P. Chekhov) and Ivan Ivanovich (the short story Иван Ивановичwritten by L. N. Andreev). It describes the development from an inocent man towards a dangerous type the spinelessness of whom maltreats the others.